2014
DOI: 10.1073/pnas.1408355111
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation of BDNF as a biomarker of early-life adversity

Abstract: Early-life adversity increases the risk for psychopathology in later life. The underlying mechanism(s) is unknown, but epigenetic variation represents a plausible candidate. Early-life exposures can disrupt epigenetic programming in the brain, with lasting consequences for gene expression and behavior. This evidence is primarily derived from animal studies, with limited study in humans due to inaccessibility of the target brain tissue. In humans, although there is evidence for DNA methylation changes in the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
252
2
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 368 publications
(287 citation statements)
references
References 59 publications
(88 reference statements)
27
252
2
6
Order By: Relevance
“…26 While previous studies have indicated increased NR3C1 1F DNA methylation in cord blood samples at birth, here we illustrate that increased NR3C1 1F DNA methylation associated with prenatal depression persists into the postnatal period in infant buccal cells, independent of postnatal depressed maternal mood, and is particularly evident in male infants. Previous studies in humans have not examined the question of sex differences in environmentally-induced NR3C1 1F DNA methylation, [23][24][25][26][27] and although animal studies have primarily examined these effects exclusively in males, there is emerging evidence suggestive of a particular epigenetic vulnerability in males in response to prenatal 33 and postnatal 35 experiences. These findings compliment a body of literature, which suggests that males may more be at risk of adverse outcomes compared to females as a result of exposure to maternal distress during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…26 While previous studies have indicated increased NR3C1 1F DNA methylation in cord blood samples at birth, here we illustrate that increased NR3C1 1F DNA methylation associated with prenatal depression persists into the postnatal period in infant buccal cells, independent of postnatal depressed maternal mood, and is particularly evident in male infants. Previous studies in humans have not examined the question of sex differences in environmentally-induced NR3C1 1F DNA methylation, [23][24][25][26][27] and although animal studies have primarily examined these effects exclusively in males, there is emerging evidence suggestive of a particular epigenetic vulnerability in males in response to prenatal 33 and postnatal 35 experiences. These findings compliment a body of literature, which suggests that males may more be at risk of adverse outcomes compared to females as a result of exposure to maternal distress during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…41 Although species differences in the regulation of this gene may account for our findings, recent analyses indicate increased DNA methylation in human cord blood samples within the CREB binding site associated with elevated in utero BPA exposure, which is consistent with the direction of reported effects in rodents. 33 An alternative explanation for these findings may involve the biphasic epigenetic changes that have been observed to occur across development. 42 The decreased BDNF methylation we observe in infants exposed to prenatal depression could reflect a molecular basis for the rapid maturation that may be induced by adverse prenatal events.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Expression of this gene is reduced in Alzheimer's, Parkinson's, and Huntington's disease patients. Nowadays, this gene has been demonstrated to possibly be involved in the regulation of the stress response and in the biology of mood disorders [27,28]. It has been hypothesized that BDNF is involved in the pathogenesis of ADHD, although the study results are controversial.…”
Section: Differential Expression Of Lncrnas and Targeted Mrnas Of Bdnmentioning
confidence: 99%